A brief massive aggregation of pelagic swimming crabs Euphylax dovii (Decapoda: Portunidae) at Cocos Island, Costa Rica coincides with onset of El Niño event - Hearn, Alex (2020)
Introduction: Sporadic aggregations of decapod crustaceans can occur for various reasons and in some cases their drivers are poorly understood. Objective: Here, we present our observations of an apparently rare massive aggregation of pelagic swimming crabs, Euphylax dovi.  Methods: During a research cruise at Cocos Island (5°32’34” N, 87°05’06” W), we encountered large numbers of E. dovii in surface waters in the evenings of May 6-7, 2015, some of which we collected for identification prior to returning to the water. Results: Crabs of both sexes were identified, yet no females were bearing eggs. Crabs aggregated around a small dinghy used for scientific surveying from 4pm through 8pm each evening, and around our research vessel throughout the night, presumably attracted by the lights. On both occasions, the aggregation dissipated around dawn. Crabs were not seen prior to or after the two nights. Conclusions: Sea surface temperatures at Cocos during this period were markedly warm, with no perceptible thermocline down to at least 40 m, coinciding with the onset of the 2015 El Niño event. It appears that the aggregation formed in response to El Niño conditions, yet the biological reason behind it remains unknown.